Production of 5-Hydroxymethylfurfural from cassava flour with deep eutectic solvent (DES) molar variations - Mochamad Bagus Hermanto; Dina Wahyu Indriani; Anida Apriliani Simamora (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
In the past few years, 5-Hydroxymethylfurfural (5-HMF) has been used in many industrial practices as a substitution for plastics and a versatile precursor for synthesis into a variety of value-added chemicals and fuels. The potential use of glucose monomers from cassava (Manihot uttilisma) as a potential source for 5-HMF production needed to be considered. Deep Eutectic Solvent (DES) is natural, environmentally friendly, easy to obtain, and it was used as a solvent to increase the 5-HMF yield. Therefore, the objectives of this research are to obtain the 5-HMF from cassava flour with the suitable molar ratio of the DES solvent and to analyze the effect of the addition of DES solvent on the yield of 5-HMF. The synthesis of DES was based on choline chloride with ethylene glycol with a molar ratio of 1:2, 1:3, and 1:4 and was suitable for use as a solvent in the 5-HMF dehydration process. The ratio of glucose: DES of 1:6 affects the 5-HMF yield with the highest yield was 78.61% at a glucose concentration of 51.24% and the lowest without DES was 44.49% with the same glucose concentration.